A multicenter, randomized, and double-blind phase IV clinical trial to compare the efficacy and safety of fixed-dose combinations of amlodipine orotate/valsartan 5/160 mg versus valsartan/hydrochlorothiazide 160/12.5 mg in patients with essential hypertension uncontrolled by valsartan 160 mg monotherapy. Issue 37 (September 2018) - Ahn, Youngkeun; Kim, Yongcheol; Chang, Kiyuk; Kim, Weon; Rhee, Moo-Yong; Cha, Kwang Soo; Hyon, Min Su; Shim, Chi Young; Lee, Sung Yun; Kim, Doo Il; Kim, Sang Wook; Lim, Sang-Wook; et al.
Abstract: Background: To determine whether the effectiveness and safety of fixed-dose combinations (FDCs) of amlodipine orotate/valsartan (AML/VAL) 5/160 mg are noninferior to those of valsartan/hydrochlorothiazide (VAL/HCTZ) 160/12.5 mg in hypertensive patients with inadequate response to valsartan 160 mg monotherapy. Methods: This 8-week, active-controlled, parallel-group, fixed-dose, multicenter, double-blind randomized controlled, and noninferiority trial was conducted at 17 cardiovascular centers in the Republic of Korea. Eligible patients had mean sitting diastolic blood pressure (msDBP) ≥90 mm Hg despite monotherapy with valsartan 160 mg for 4 weeks. Patients were randomly assigned to treatment with AML/VAL 5/160 mg FDC (AML/VAL) group or VAL/HCTZ 160/12.5 mg FDC (VAL/HCTZ) group once daily for 8 weeks. A total of 238 patients were enrolled (AML/VAL group, n = 121; VAL/HCTZ group, n = 117), of whom 228 completed the study. Results: At 8 weeks after randomization, msDBP was significantly decreased in both groups (−9.44 ± 0.69 mm Hg in the AML/VAL group and −7.47 ± 0.71 mm Hg in the VAL/HCTZ group, both P < .001 vs baseline). Between group difference was −1.96 ± 1.00 mm Hg, indicating that AML/VAL 5/160 mg FDC was not inferior to VAL/HCTZ 160/12.5 mg FDC at primary efficacy endpoint. Control rate of BP defined as the percentage of patients achieving mean sitting SBP (msSBP) <140 mm Hg or msDBP <90 mm Hg (target BP) from baseline to week 8 was significantly higher in the AML/VAL group than that in the VAL/HCTZ group (84.3% [n = 102] in the AML/VAL group vs 71.3% [n = 82] in the VAL/HCTZ group, P = .016). At 8 weeks after randomization, mean uric acid level was significantly increased in the VAL/HCTZ group compared to that at baseline (0.64 ± 0.08 mg/dL; P < .001). However, it was slightly decreased from baseline in the AML/VAL group (−0.12 ± 0.08 mg/dL; P = .085). The intergroup difference was significant ( P < .001). Conclusion: The effectiveness and safety AML/VAL 5/160 mg FDC are noninferior to those of VAL/HCTZ 160/12.5 mg FDC in patients with hypertension inadequately controlled by valsartan 160 mg monotherapy.